If it's not what You are looking for type in the equation solver your own equation and let us solve it.
35=4(5x-2)+3
We move all terms to the left:
35-(4(5x-2)+3)=0
We calculate terms in parentheses: -(4(5x-2)+3), so:We get rid of parentheses
4(5x-2)+3
We multiply parentheses
20x-8+3
We add all the numbers together, and all the variables
20x-5
Back to the equation:
-(20x-5)
-20x+5+35=0
We add all the numbers together, and all the variables
-20x+40=0
We move all terms containing x to the left, all other terms to the right
-20x=-40
x=-40/-20
x=+2
| -7=3(x+3)-7 | | 4(4x+1)=-3x+42 | | 3b=5b=90 | | -5x+7=4(2x+5) | | 30=2(2x-1) | | -9x-15=-6x-36 | | -2x+26=3x-4 | | 7x^2-67x-108=0 | | 3x+68÷8=x+6 | | Z=y-5 | | 5(x+2)-8=4x-7 | | 3x/2=2/3 | | 2x-8=6x-16 | | 6r+37=13-7r | | 34=k–9 | | 7x-2x(x+1)=6x+14 | | 16x-14-9x=13 | | 2/3t=5/3 | | x^2+3x/5x+9=12 | | d–13=41 | | s–4.1=18.5 | | -15a-6-11+4a=0 | | (2/x)-10=12 | | 625÷w=25 | | 3x+8=15x | | u–26=29 | | 137+z=731 | | 1/3x-2=-3/5x-9 | | 2=6–2s | | -2x^2+23=7 | | 4p-49=7(-2p+2) | | 3+6x=-2x+29 |